Cognitive Improvement Through Non-Invasive Brain Stimulation Techniques in Healthy Adults - Kurniawan, Willytiyo; Jixiong, Cai; Abdullah, Asriana; Wei, Zhang; Sari, Famella (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Cognitive enhancement is an effort to improve or improve mental functions such as memory, attention, problem solving, language, and other thinking skills. In healthy adults, the goal of cognitive enhancement is to improve current mental abilities, increase productivity, and prolong periods of mental clarity. This research was conducted with the aim of exploring various non-invasive brain stimulation techniques such as tDCS, TMS, and tACS, which offer innovative ways to improve various aspects of cognitive function without the need for invasive procedures. While there are many potential benefits, it is important to understand the long-term effects, optimize use methods, and ensure use of this technology is safe and ethical. The method used by researchers in researching Cognitive Improvement Through Non-Invasive Brain Stimulation Techniques in Healthy Adults is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. The results of data acquisition will also be tested again using the SPSS application. From the research results, it can be seen that this research is an interesting and continuously developing field in neuroscience and psychology today. With non-invasive brain stimulation techniques, it is possible to stimulate certain areas of the brain, thereby further improving cognitive functions such as memory, attention and problem solving in healthy adults. From this study, researchers can conclude that non-invasive brain stimulation, such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), has been proven to improve motor and cognitive function in healthy adults. Recent research shows that tDCS can modulate the brain's motor cortex, which functions to increase intelligence in healthy adults.